The creativity code : art and innovation in the age of AI - Du Sautoy, Marcus (The Belknap Press of Harvard University Press, 2019)
Most books on AI focus on the future of work. But now that algorithms can learn and adapt, does the future of creativity also belong to well-programmed machines? To answer this question, Marcus du Sautoy takes us to the forefront of creative new technologies and offers a more positive and unexpected vision of our future cohabitation with machines.--